IMPROVE THE PROMOTION STRATEGY OF KAN JABUNG - Faiqotul Ummah; Charistantya Iddo; Abdul Wahab Hakimy; Shelma Amalia; Tommy Minggus; Ludovica Fortunata Cutrona (International Journal of Applied Business and International Management, 2018)
KAN Jabung is a cooperative established in 1979. KAN Jabung is a cooperatives that run several business. But, the main business for KAN Jabung is product from cow. Producing dairy milk for people is one of the core business. Lately, milk is become a vital need for people. Milk is the best way to maintain human good health. Delicious taste will never bored people who consume milk. In fact, milk consumption is raising year by year. But, people in the outskirt of the town still has a minimum consumption. So, team 22 think a strategy that suit in these facts. The strategy is going to take an advantage from minimal educating about milk. Milk nutrition isn’t just about the vitamin or calcium, but natural nutrition from milk still brought by the pasteruate ways. Because in UHT way, the nutrition is wasted because of heat and the company has to fill artificial nutrition and in people mindset natural is always better than artificial. Our effort is based on KAN Jabung vision and mission. Being competitive agribusiness cooperatives, and grow sustainably is KAN Jabung vision. This vision means that KAN Jabung has to improving steadily and sustain the profit. Taking segment in family and kids, KAN Jabung hope is to penetrate this product until accepted by citizen in uptown and downtown.